2013
DOI: 10.1016/j.fob.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Activating types 1 and 2 angiotensin II receptors modulate the hypertrophic differentiation of chondrocytes

Abstract: A local tissue-specific renin–angiotensin system (local RAS) has been identified in many organs. However, no report has described the role of a local RAS in the hypertrophic differentiation of chondrocytes. To examine the role of a local RAS in the hypertrophic differentiation, we activated angiotensin II type 1 receptor (AT1R) and angiotensin II type 2 receptor (AT2R) separately in the cell line ATDC5, which involves differentiation from mesenchymal stem cells to hypertrophic chondrocytes. Activation of AT1R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
(30 reference statements)
3
16
0
Order By: Relevance
“…ACE expression is induced in the chondrocytes of bone callus during fracture healing, which suggests AngII signaling is involved in endochondral bone formation. Recently, Tsukamoto group showed that Atgr1 suppressed the hypertrophic differentiation of chondrocytes in vitro [35], which is consistent with our observation that blockage of Agtr1 accelerated hypertrophic differentiation during endochondral bone formation. The accelerated hypertrophy in Losartan treated growth plates may be attributed to alteration in the expression of matrix protein like Col10a1, or may be due to changes in matrix protein metabolism, which was suggested by AngII regulation on matrix metalloproteinase during cardiac remodeling or hypertension [3638].…”
Section: Discussionsupporting
confidence: 91%
“…ACE expression is induced in the chondrocytes of bone callus during fracture healing, which suggests AngII signaling is involved in endochondral bone formation. Recently, Tsukamoto group showed that Atgr1 suppressed the hypertrophic differentiation of chondrocytes in vitro [35], which is consistent with our observation that blockage of Agtr1 accelerated hypertrophic differentiation during endochondral bone formation. The accelerated hypertrophy in Losartan treated growth plates may be attributed to alteration in the expression of matrix protein like Col10a1, or may be due to changes in matrix protein metabolism, which was suggested by AngII regulation on matrix metalloproteinase during cardiac remodeling or hypertension [3638].…”
Section: Discussionsupporting
confidence: 91%
“…However, in contrast to bone, little is known about the effects of Ang II on chondrocytes and cartilage despite the existence of Ang II receptors in chondrocytes. 12,13 Various reports suggest the importance of RAS in chondrocytes. An anti-arthritic effect of blockade of RAS by ARBs has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no report indicating the role of AT2R in vivo, previous in vitro experiments using ATDC5 demonstrated that activation of AT2R enhanced hypertrophic differentiation. 13 It was demonstrated that stimulation by Ang II and activation of AT1R suppressed hypertrophic differentiation of chondrocytes. This is the opposite result to our present data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiotensin converting enzyme 2 (ACE2) converts angiotensin Ⅱ (AngⅡ) into peptides including angiotensin-1-7 (Ang1-7) and angiotensin-1-9 that counteract the effects of Ang Ⅱ through Mas receptor (MasR) and angiotensin type II receptor (AT2R) respectively [8, 9]. ACE2 activity and expression level were reported to be severely down regulated or absent in proliferating alveolar epithelial cell lines A549 and MLE-12, while its activity and expression level went much higher in quiescent A549 and MLE-12 cells [10].…”
Section: Introductionmentioning
confidence: 99%